PKM PENDAMPINGAN GURU PENGGERAK DALAM PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN APLIKASI ARTICULATE STORYLINE 3 DI KOTA BANDUNG - Dahlan, Taufiqulloh; Dheni Harmaen; Acep Roni Hamdani; Erni Kustiani; Ine Pebriyanti; Pia Puspitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This community service program (PKM) aims to assist "Guru Penggerak" in Bandung in developing interactive multimedia-based learning media using the Articulate Storyline 3 application. The use of interactive multimedia-based learning media is expected to improve the effectiveness of the learning process and student engagement. The activities involve several stages, including basic training, hands-on practice, technical assistance, and evaluation of the results. The results of this activity show an increase in the ability of "Guru Penggerak" to use Articulate Storyline 3 to create more attractive and interactive learning materials. Additionally, this program strengthens the teachers' competence in utilizing educational technology in line with the development of the digital era.